Straight talk on leadership solving Canada's business crisis - Williamson, R. Douglas (Wiley, 2013)
An urgent wake-up call--and radical action plan--for business leaders everywhere While it focuses primarily on Canadian business, this important book shares valuable insights of benefit to transformational business leaders everywhere. Without sugar coating his message, author R